Skötsel av älgskadade bestånd - Skoog, Johan (SLU/Dept. of Silviculture, 2005)
Sweden has today the highest moose (Alces alces) population in the world. The population has been very high since the late seventies and in the beginning of the eighties there was a big "moose explosion". The main food source for moose during the winter is young pine (Pinus sylvestris) and birch (Betula spp.). The high moose population has therefore lead to high damage on pine forests over big areas. These forests are now about to be commercial thinned for the first time. Because of that the difficult, but important question of how to manage these damaged forests in the best way arises.